THE ANALYSIS OF COST EFFICIENCY LEVELS OF SHARIA BANKS WITH STOCHASTIC FRONTIER ANALYSIS METHODS FOR THE 2015-2018 PERIOD - Devy Ariesta Putri; Sylva Alif Rusmita (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to determine the cost efficiency level of Sharia Commercial Banks registered in the OJK for the 2015-2018 period. This study uses a quantitative approach. This study uses a parametric approach to measure the cost efficiency of Islamic banking with the stochastic frontier analysis (SFA) method. The value of cost efficiency using the SFA method is in the form of a value of 100%, the closer it is to the value of 100%, the more efficient the bank works. The analysis technique used is the cross-section model and panel model. This study uses 7 Sharia Commercial Bank samples. Data obtained from each of the Sharia Commercial Bank Financial Report websites. The results of the Cross-Section Stochastic Frontier Analysis analysis on cost efficiency show the average value of the efficiency of Islamic banking in Indonesia approaching 95.92%. The results of the cost-efficiency analysis show that Islamic banking in the 2015-2018 period tended to be less efficient in controlling costs.Keywords: Cost efficiency, Islamic commercial banks, Stochastic Frontier Analysis (SFA).REFFERENCE Agnesty, T., & Budi, Z. M. (2011). Efisiensi biaya dan efisiensi profit pada unit usaha syariah (UUS) dengan metode Stochastic Frontier Analysis (SFA) tahun 2007-2011. Depok: Fakultas Ekonomi dan Bisnis Universitas Indonesia.Aigner, D., Lovell, C. A. K., & Schmidt, P. (1977). Formulation and estimation of stochastic frontier production function models. Journal of Econometrics, 6(1), 21–37. https://doi.org/10.1016/0304-4076(77)90052-5Bank Indonesia. (1998). Undang-Undang Republik Indonesia No 10 Tahun 1998 Tentang Perubahan Atas Undang-Undang No 7 Tahun 1992 Tentang Perbankan. Jakarta: Bank Indonesia.Berger, A. N., & Bonaccorsi di Patti, E. (2006). Capital structure and firm performance: A new approach to testing agency theory and an application to the banking industry. Journal of Banking and Finance, 30(4), 1065-1102. https://doi.org/10.1016/j.jbankfin.2005.05.015Berger, A. N., & Humphrey, D. B. (1997). Efficiency of financial institutions: International survey and directions for future research. European Journal of Operational Research, 98(2), 175-212. https://doi.org/10.1016/S0377-2217(96)00342-6Berger, A. N., & Mester, L. J. (1997). Inside the black box: What explains differences in the efficiencies of financial institutions? Journal of Banking and Finance, 21(7), 895-947. https://doi.org/10.1016/S0378-4266(97)00010-1Coelli, T. J. and D. S. P. R. (2003). Total Factor Productivity Growth in Agriculture: A Maninquist Index Analysis of 93 Countries. Agricultural Economics, 32(1), 115-134. https://doi.org/10.1111/j.0169-5150.2004.00018.xEfendy, M. (2009). Manajemen suatu pendekatan berdasarkan ajaran islam. Jakarta: Bhratara Karya Aksara.Hadad, M. D., & Wimboh Santoso, Eugenia Mardanugraha, D. I. (2003). Pendekatan parametrik untuk efisiensi perbankan Indonesia. Bank Indonesia, 1–27. Retrieved from https://www.bi.go.id/id/publikasi/perbankan-dan-stabilitas/riset/Pages/Pendekatan parametrik untuk efisiensi Perbankan Indonesia.aspxHartono, E. (2009). Analisis Efisiensi Biaya Industri Perbankan Indonesia Dengan Menggunakan Metode Parametrik Stochastic Frontier Analysis. Tesis tidak diterbitkan. Semarang: Program Pascasarjana Universitas Diponegoro.Huri, M. D., & Susilowati, I. (2004). Pengukuran efisiensi relatif emiten perbankan dengan metode Data Envelopment Analysis (studi kasus: bank-bank yang terdaftar di Bursa Efek Jakarta tahun 2002). Dinamika Pembangunan, 1(2), 95-110.Karim, A. A. (2014). Ekonomi mikro Islami. Jakarta: RajaGrafindo Persada.Khumbakar, S.C., dan Lovell, C. A. K. (2003). Stochastic frontier analysis. United Kingdom: Cambridge University Press.Kurnia, A. S. (2004). Mengukur efisiensi intermediasi sebelas bank terbesar indonesia dengan pendekatan Data Envelopment Analisis (DEA). Jurnal Bisnis Strategi, 13(2), 126–140.Srairi, S. A. (2010). Cost and profit efficiency of conventional and Islamic banks in GCC countries. Journal of Productivity Analysis, 34(1), 45-62. https://doi.org/10.1007/s11123-009-0161-7Witono. (1999). Beberapa Alternatif Pendekatan untuk Mangukur Efisiensi atau In-Efisiensi dalam Usahatani. Informatika Pertanian, 8.